Corneal tattooing: an alternative treatment for disfiguring corneal scars. Issue 4 (1st April 2002) - Pitz, S; Jahn, R; Frisch, L; Duis, A; Pfeiffer, N
Abstract : Background: The performance and results of corneal tattooing are described in a case series of 11 patients suffering from a disfiguring corneal scar using a technique similar to conventional dermatography. Methods: Drawing ink in different shades was applied into the anterior corneal stroma by punctures performed with a conventional spatula needle. Results: Up to 4 years after surgery all patients still had satisfactory staining of the formerly cosmetically disfiguring corneal scar. Conclusion: Tattooing of unsightly corneal scars proved to be an efficient and easy to perform technique, yielding acceptable results during follow up.